Next job, best job : a headhunter's 11 strategies to get hired now - Barnett, Rob (Entrepreneur) (Citadel Press, Kensington Publishing Corp., 2021)
"This decade opened with a global health crisis, mass unemployment, political disruptions, federal budget deficits, and unprecedented economic uncertainty, with even the most optimistic predictions anticipating delayed economic recovery and uncertainty into the 2030s. The Covid-19 pandemic has both decimated the job market and permanently changed the future of the workplace, with tens of millions of qualified, competent, and loyal employees fired, furloughed, job eliminated, or restructured. Getting a new job is more competitive than ever. Headhunter Rob Barnett has the answer. Next Job, Best Job goes beyond the tired, old job search methods and provides a blueprint to easily rewriting your entire work history and building a resume and LinkedIn profile that will sell you better than ever. Barnett shares the secrets of how to master the perfect, 30-minute job interview, and imparts priceless advice on how to negotiate the best offer and close like a pro. With a mix of straight talk, much-needed humor, and compassion, Next Job, Best Job offers concrete steps that job seekers can take to best position themselves in a transformed marketplace. With a steady dose of love and practical wisdom, Rob Barnett will inspire readers to stop whining, start winning, and find the job of their dreams"--